Invasões biológicas: indo além dos modelos de distribuição na busca de predições realistas sob restrições energéticas - Andrade, André Felipe Alves de (2020)
Biological invasions are one of the mains threats to biodiversity in the Anthropocene. The introduction of new exotic species might have serious consequences to native communities, being responsible for modifications to the established biotic relations up to the extinction of native species. Apart from serious ecological consequences, invasive species are also relevant form the economic point of view, as many species reach high populational levels which can lead to losses for several economic activities, such as agriculture and hydroelectric energy generation. Given the relevance of invasive species, an essential aspect to reduce the losses caused by biological invasions is to get ahead of the invasion process and prevent a potential invasive species from ever reaching a new region. In order to reach this goal, the different methods should be effective in anticipating possible invasions, by accurately defining target regions and also how the invasive species will interact with the native community. In this thesis we built and tested several models that seek to improve our capability to anticipate the results of an invasion process in its several stages. In the first chapter we explored the capability of ecological niche models (ENMs) in identifying suitable areas for the occurrence of a potential invasive species. ENMs are commonly used for establishing areas of interest, based on species’ suitability. However, as we demonstrate in this first chapter, mismatches between the realized and the fundamental niche may lead to patterns of consistent under-or overprediction of the areas considered as harbouring suitable climatic conditions for an invasive species. At the second chapter we explored how the interaction between the different life-history strategies of invasive species and the native community determine invasion success. We’ve built a realistic system in which individuals compete for energy and have priorities for allocating the obtained energy. The whole system is regulated by allometric relations and energetic budgets. We found that invaders that share a common life-history strategy with the native species were more successful in establishing in the system, being that the strategy with the higher gains was of living longer, accumulating reserves while reducing the reproductive output (less offspring with longer gestation periods). At the third chapter we explored how those life-history strategies behave under a realistic landscape, with a real land-use and fluctuations in the energy within the system. In this chapter we’ve improved the chapter developed at the chapter 2 and focused on answering questions related to the landscape configuration and invasive-native co-occurrence under different levels of landscape heterogeneity. We also evaluated our model under classical hypothesis related to the invasion process. We’ve evaluated invasion success over 18 years in a landscape undergoing a rapid agriculture expansion and found that invasion success was highest at the end of this period, when the landscape is with its highest agriculture coverage. Agriculture expansion, by itself, was responsible for the extinction of native species, besides increasing invasion success and the co-occurrence between invasive and native species. There was also a difference in successful life-history strategies, in a way that the spatial configuration plays a big role in determining invasion success.